A fellowship of Ring1 maintains AML stem cells - Heery, David M. (American Society of Hematology, 2018)
Polycomb repressive complex 1 (PRC1) and PRC2 are transcriptional repressors that function as key regulators of the self-renewal and differentiation (cell lineage specification) pathways in stem cells. In this issue of Blood, Shima et al1 report that 2 ubiquitin ligases (Ring1A and Ring1B), which are key components of PRC1 complexes, are essential for the establishment and maintenance of acute myeloid leukemia (AML) in mouse models.